Rancang Bangun Aplikasi Mobile Media Informasi Wisata Suroboyo Carnival Berbasis Augmented Reality - Alfin Noor Afyuddin; Issa Arwani; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Tourism includes human needs and becomes an important sector for generating regional and state revenues. In general, tourists use print media to obtain information and become a guide in a tourist location. But the media has limitations, so it needs an interactive and effective media to be used as a medium of information of a tourist location. Auxiliary media is an application that provides navigation features that show the direction and distance of the user location with the location of the intended rides as well as suggestions of the order of visits and information of the required rides. The media used are smartphones by utilizing augmented reality technology as well as the use of combinations, permutations and algorithms dijkstra to suggest the order of visits with the shortest path. Features used Android smartphone is a camera, GPS, accelerometer, and compass. System design using the framework beyondAR. Testing on the system in the form of functional testing, angle accuracy testing, and distance accuracy testing. The function of determining the direction and distance with the markers and suggestions of the order of visits can run. On the results of the results of accuracy test results arising from the implementation of the formula heading on the application has a percentage of accuracy of 97.43%. And on the test of accuracy of distance has the accuracy percentage of 99.79% with distance calculation using haversine method. Accuracy test results show the implementation on the system has a high accuracy.